2010
DOI: 10.1590/s0104-77602010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Use of wood from Pinus caribaea var. caribaea and Pinus caribaea var. bahamensis for production of particleboard panels

Abstract: This study aimed to evaluate the quality of particleboard panels made with wood from Pinus caribaea var. caribaea and Pinus caribaea var. bahamensis, as obtained from forest stands. Experimental panels were produced with a nominal density of 0.70 g/cm³, using urea-formaldehyde resin and wood particles of Pinus caribaea var. caribaea and Pinus caribaea var. bahamensis, at rates of 100%x0%, 75%x25%, 50%x50%, 25%x75% and 0%x100%. Pinus taeda wood was used as control sample. Panels were compressed at a specific pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
1
6
1
3
Order By: Relevance
“…They can also be classified as structural use panels and special structural use panels for use in dry conditions, which require TS values after 24 h of immersion below 16% and 15%, respectively. The average water absorption values in this study were lower than those presented by Iwakiri et al (2010) for panels produced with three different species of pine and ureaformaldehyde resin (UF), which ranged from 83.74% to 90.67% after 24 h of immersion. They were also lower than the average values reported by Okino et al (2000), who produced panels using Hevea brasiliensis wood with urea-formaldehyde resin and found average 2-and 24-h WA values ranging from 39.8% to 61.1% and 61.3% to 74.3%, respectively.…”
Section: Thickness Swelling (Ts)contrasting
confidence: 76%
See 2 more Smart Citations
“…They can also be classified as structural use panels and special structural use panels for use in dry conditions, which require TS values after 24 h of immersion below 16% and 15%, respectively. The average water absorption values in this study were lower than those presented by Iwakiri et al (2010) for panels produced with three different species of pine and ureaformaldehyde resin (UF), which ranged from 83.74% to 90.67% after 24 h of immersion. They were also lower than the average values reported by Okino et al (2000), who produced panels using Hevea brasiliensis wood with urea-formaldehyde resin and found average 2-and 24-h WA values ranging from 39.8% to 61.1% and 61.3% to 74.3%, respectively.…”
Section: Thickness Swelling (Ts)contrasting
confidence: 76%
“…Both types of boards produced should be restricted to use in dry locations. Table 7 shows values obtained by Paes et al (2011), Iwakiri et al (2010, and Okino et al (2000) for the same properties as those evaluated in the present research. Paes et al (2011) produced Pinus elliottii Engelm wood panels with bi-component polyurethane resin (PU).…”
Section: Static Bending (Sb)supporting
confidence: 61%
See 1 more Smart Citation
“…MOR, RAPf and RAPt average values to ink waste particleboard were close to Pinus sp particleboard manufactured with urea formaldehyde by Torrell et al (2013), but, for the BTH polymer particleboard, just MOR and RAPt average values were close. Iwakiri et al (2010) researched Pinus taeda particleboards with urea-formaldehyde and found to MOR, MOE and PT average values equal to 0.58 MPa, 12.03 MPa and 1866 MPa. MOR average values determined to epoxy ink waste and BTH polymer particleboards were close to the Iwakiri et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Iwakiri et al (2010) researched Pinus taeda particleboards with urea-formaldehyde and found to MOR, MOE and PT average values equal to 0.58 MPa, 12.03 MPa and 1866 MPa. MOR average values determined to epoxy ink waste and BTH polymer particleboards were close to the Iwakiri et al (2010).…”
Section: Discussionmentioning
confidence: 99%